2020
DOI: 10.1080/02699931.2020.1724893
|View full text |Cite
|
Sign up to set email alerts
|

Two facets of affective empathy: concern and distress have opposite relationships to emotion recognition

Abstract: Theories on empathy have argued that feeling empathy for others is related to accurate recognition of their emotions. Previous research that tested this assumption, however, has reported inconsistent findings. We suggest that this inconsistency may be due to a lack of consideration of the fact that empathy has two facets: empathic concern, namely the compassion for unfortunate others, and personal distress, the experience of discomfort in response to others' distress. We test the hypothesis that empathic conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 63 publications
1
48
0
4
Order By: Relevance
“…Empathy was higher also in cat owners and persons who had grown up with cats, and a significant correlation was found between the total number of correct context identifications and empathy toward cats, but not empathy toward animals in general. Greater empathy toward cats, and not just toward animals in general, could motivate the choice of a cat as a companion animal; moreover, “being empathetic” toward cats may, for example, motivate owners to shift their attention toward them more, which can thereby increase accuracy in emotion recognition as happens in humans [ 60 , 61 ]. In general, feeling empathy together with familiarity can lead perceivers to focus on expressive cues that communicate information about the feelings of others.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Empathy was higher also in cat owners and persons who had grown up with cats, and a significant correlation was found between the total number of correct context identifications and empathy toward cats, but not empathy toward animals in general. Greater empathy toward cats, and not just toward animals in general, could motivate the choice of a cat as a companion animal; moreover, “being empathetic” toward cats may, for example, motivate owners to shift their attention toward them more, which can thereby increase accuracy in emotion recognition as happens in humans [ 60 , 61 ]. In general, feeling empathy together with familiarity can lead perceivers to focus on expressive cues that communicate information about the feelings of others.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on humans show that the ability to recognize the emotional states of others from vocal and/or visual cues appears to be positively influenced by both empathy and gender. More empathic individuals are more accurate in recognizing others’ emotional states [ 59 , 60 , 61 ]. Moreover, there is evidence that women are more empathic [ 62 ] and more skilled in recognizing emotions than men [ 63 , 64 , 65 ].…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, affective empathy will be defined as the ability to be sensitive to and vicariously experience the emotional states felt by other people. These vicarious emotional responses can encompass both empathic concern (e.g., other-oriented feelings of sympathy) and personal distress (e.g., self-oriented feelings of discomfort; Grynberg & Konrath, 2020;Israelashvili et al, 2020).…”
Section: Dissociating Psychopathy and Antisocial Behavior: What Can Empathy Teach Us?mentioning
confidence: 99%
“…In other words, when patients observed others' facing adversity, they felt more personal distress leading to limited cognitive fluency. The findings of Israelashvili et al 44 showed that healthy participants who scored high on selfreport empathic concern also increased their accuracy of recognizing nonverbal facial emotions, whereas those who scored high on personal distress generally had poor performances. It may suggest that the two facets of empathic concern and personal distress have opposite influences in affective empathy.…”
Section: Discussionmentioning
confidence: 97%